2019
DOI: 10.12669/pjms.35.5.287
|View full text |Cite
|
Sign up to set email alerts
|

Association of medication administration errors with interruption among nurses in public sector tertiary care hospitals

Abstract: Objectives: To determine the association of medication administration errors with interruption among nurses working at public sector tertiary care hospitals in Karachi, Pakistan. Methods: An analytical cross-sectional study was accomplished at two public sector healthcare facilities Civil Hospital, and Dow University Hospital, Karachi. The study was carried out from October 2017 to July 2018 over a period of 10 months. The sample was calculated by using OpenEpi version 3.0. By taking 56.4% of medication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
3
2
Order By: Relevance
“…Interestingly, interruptions were not found to be significantly associated with the severity of MAEs in our study, contrary to findings from previous research [ 62 , 63 ]. For instance, prior study has reported a doubling of the estimated risk of majorly severe errors in the presence of four interruptions [ 63 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, interruptions were not found to be significantly associated with the severity of MAEs in our study, contrary to findings from previous research [ 62 , 63 ]. For instance, prior study has reported a doubling of the estimated risk of majorly severe errors in the presence of four interruptions [ 63 ].…”
Section: Discussioncontrasting
confidence: 99%
“…One plausible explanation for this contradicting finding lies in the differing prevalence of interruptions across studies. In our investigation, only 11.8% of nurses experienced interruptions or distractions during medication preparation and administration, compared to a markedly higher rate of 90.8% reported in another study [ 62 ]. Moreover, despite the implementation of interventions such as the ’Do Not Disturb’ vests and their inclusion as a parameter in the annual nursing audit in this study, adherence to wearing the safety vest remained low at 4.8%.…”
Section: Discussioncontrasting
confidence: 80%
“…Recent studies from different countries have shown that the frequency of such interference in the clinical setting is particularly high, even more than 10 times/h (Kwon et al, 2021; Lin, Hsieh, et al, 2021, Lin, Feng, et al, 2021; Sharma et al, 2021), especially during the documentation of patient care (Sasangohar, 2015). Negative effects of interference have also been reported, such as increasing the time for task completion (Campoe & Giuliano, 2017; Forsyth et al, 2018), jeopardizing patient safety (Flynn et al, 2016; Raja et al, 2019), and psychological and cognitive overload of nurses (Kim et al, 2019). Solutions have been developed to reduce the occurrence of interference, such as the Sterile Cockpit (Hohenhaus & Powell, 2008), No Interruption Zone (Anthony et al, 2010), Do Not Disturb Vest (Craig et al, 2013), Task‐Severity Awareness Tool (Sasangohar, 2015), and other interventions for medication verification and administration tasks (Kavanagh & Donnelly, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are often interrupted during MA, with observational studies finding interruption rates of 94.51 percent (Zhao et al, 2019) and 99 percent (M. Johnson, Sanchenz et al, 2017) for nurses in hospital settings. Interruptions are associated with an increased frequency (Raja et al, 2019;Westbrook et al, 2010) of medication administration errors (MAEs), placing patient safety at risk. Not surprisingly, interruptions also lead to increased nursing task completion times, resulting in decreased task efficiency (Cooper et al, 2016).Interventions aimed to reduce interruptions during the MA process have been implemented in health care settings, such as nurses donning "do not disturb" vests or preparing medication in "nointerruption zones."…”
mentioning
confidence: 99%
“…Nurses are often interrupted during MA, with observational studies finding interruption rates of 94.51 percent (Zhao et al, 2019) and 99 percent (M. Johnson, Sanchenz et al, 2017) for nurses in hospital settings. Interruptions are associated with an increased frequency (Raja et al, 2019;Westbrook et al, 2010) of medication administration errors (MAEs), placing patient safety at risk. Not surprisingly, interruptions also lead to increased nursing task completion times, resulting in decreased task efficiency (Cooper et al, 2016).…”
mentioning
confidence: 99%